Prevalence and factors associated with anogenital warts among sexual and gender minorities attending a trusted community health center in Lagos, Nigeria - Sylvia B. Adebajo; Rebecca G. Nowak; Ruxton Adebiyi; Elizabeth Shoyemi; Charles Ekeh; Habib O. Ramadhani; Charlotte A. Gaydos; Julie A. Ake; Stefan D. Baral; Manhattan E. Charurat; Trevor A. Crowell (Public Library of Science (PLoS), 2022)
Anogenital warts caused by human papillomavirus are common in sexual and gender minorities (SGM). The prevalence of, and factors associated with warts were described for SGM with a high burden of HIV in Nigeria. Individuals who reported anal sex with men were enrolled in the TRUST/RV368 cohort. Participants completed an interviewer-led survey, provided biological samples, and had a physical examination. Specific to the Lagos site, clinic staff offered standardized warts treatment services. RDS-weighted multivariable logistic regression was used to estimate the adjusted odds ratios (AORs) and 95% confidence intervals (CIs) for factors potentially associated with anogenital warts. Of 672 enrolled SGM, 478 (71%) engaged in warts services and had complete data. The median age (interquartile range) was 22 (20-26) years, 272 (52%) initiated sex before age 18, and 347 (79%) were cisgender men. Multiple male sexual partners in the previous year were reported by 448 (90%) of the participants, and 342 (66%) were living with HIV. Warts were diagnosed in 252 (54%), including anal warts in 234 (43%) and penile warts in 44 (8%); 26 (5%) had both anal and penile warts. Factors independently associated with warts included HIV (AOR:2.97; CI:1.44-6.14), engaging in receptive anal sex (AOR:3.49; CI:1.25-9.75), having multiple male sexual partners (AOR:7.26; CI:2.11-24.87), age at sexual debut (AOR:0.53; CI:0.28-0.98), and non-binary gender identity (AOR:0.20; CI:0.05-0.71). Warts were common among SGM in Nigeria, particularly those living with HIV. Administration of HPV vaccination before sexual debut or as a catch-up vaccination may prevent HPV-associated complications.